2019
DOI: 10.2217/nnm-2018-0258
|View full text |Cite
|
Sign up to set email alerts
|

Matryoshka-Type Gastro-Resistant Microparticles for The Oral Treatment of Mycobacterium Tuberculosis

Abstract: Aim: Production of Matryoshka-type gastroresistant microparticles containing antibiotic-loaded PLGA nanoparticles against Mycobacterium tuberculosis. Materials &methods: The emulsification and evaporation methods were followed for the synthesis of PLGA nanoparticles and methacrylic acid-ethyl acrylate-based coatings to protect rifampicin from degradation under simulated gastric conditions. Results & Conclusion:The inner antibiotic-loaded nanoparticles here reported can be released under simulated intestinal co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 41 publications
1
13
0
Order By: Relevance
“…Antimicrobial loaded NPs can offer some advantages over conventional antimicrobial treatments such as protection from clearance and enzymatic/chemical/surfactant inactivation, improved muco-adhesion and the ability to penetrate cell membranes [32,33] and biofilms [34], they present enhanced intracellular retention and improve the specific delivery to the site of infection. In the current work, we have shown that by using a single emulsion solvent evaporation technique, cloxacillin loaded PLGA NPs can be prepared with encapsulation efficiency (20.5 ± 1.2 % w/w), which is similar to what we recently demonstrated for rifampicin [17]. Using other antimicrobials, it has been previously reported that both single and double emulsion enable the preparation of drug loaded NP with high encapsulation efficiency but reduced drug loadings (DL; usually <5-10 wt.%) [35].…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Antimicrobial loaded NPs can offer some advantages over conventional antimicrobial treatments such as protection from clearance and enzymatic/chemical/surfactant inactivation, improved muco-adhesion and the ability to penetrate cell membranes [32,33] and biofilms [34], they present enhanced intracellular retention and improve the specific delivery to the site of infection. In the current work, we have shown that by using a single emulsion solvent evaporation technique, cloxacillin loaded PLGA NPs can be prepared with encapsulation efficiency (20.5 ± 1.2 % w/w), which is similar to what we recently demonstrated for rifampicin [17]. Using other antimicrobials, it has been previously reported that both single and double emulsion enable the preparation of drug loaded NP with high encapsulation efficiency but reduced drug loadings (DL; usually <5-10 wt.%) [35].…”
Section: Discussionsupporting
confidence: 83%
“…Empty PLGA nanoparticles had no inhibitory activity on bacterial growth in the MIC assay. However, in our previous work [17], empty PLGA-NPs showed intrinsic antituberculosis activity. This effect was attributed to the potential accelerated hydrolysis of the ester bonds of the PLGA, hence producing lactic and glycolic acids that would further acidify the media being this process autocatalytic [43].…”
Section: Discussionmentioning
confidence: 75%
“…The inner core bearing the antibiotic is released under specific intestinal conditions whereas the outer coating protects them from degradation. Oral administration of this drug delivery system ensures the sustained release of rifampicin and subsequent effect against Mycobacterium tuberculosis [104].…”
Section: Application Spectrum Of Oral Nanostructures For Treatment Ofmentioning
confidence: 99%
“…Some of them are pHdependent and remain protonated and insoluble in the stomach but dissolve in the intestine, others are mucoadhesive in the intestinal lining and being insoluble they erode over time providing with a time-controlled targeted release of the encapsulated active principle. We have previously encapsulated Rif within pH-dependent methacrylate-based microparticles (i.e., Eudragit® L100-55) and demonstrated their antibiotic protection against simulated gastric fluid (SGF) being the active antibiotic able to cross an in vitro model of intestinal barrier 11 . Compared to the oral administration in human subjects of the free drug and the equivalent dose of Rif encapsulated in Eudragit® S100, a superior bioavailability and sustained release were demonstrated 12 .…”
Section: Introductionmentioning
confidence: 99%